MATERIAL CULTURE OF UZBEKS AND TAJIKS IN AFGHANISTAN: AN ETHNOGRAPHIC ANALYSIS OF TRADITIONAL FOODS (American Journal of Research in Humanities and Social Sciences, 2026)
This article provides an ethnographic analysis of traditional foods that occupy an important place in the material culture of Uzbeks and Tajiks living in Afghanistan. The study is based on field research and oral sources and examines the regional and cultural characteristics of such dishes as osh (pilaf), shurpa, tandoor-based dishes, dough-based foods, and various types of bread. In addition, the role of food in social life, its connection with hospitality, rituals, and everyday practices is explored. The findings demonstrate that the traditional foods of Uzbeks and Tajiks in Afghanistan represent a significant cultural heritage reflecting their lifestyle and ethnic identity.